GAMBARAN FREKUENSI KONSUMSI SUPLEMEN ERGOGENIK DAN UKURAN LINGKAR OTOT LENGAN ATAS PADA PESERTA FITNESS CENTER MEDAN SEHAT TAHUN 2016 - Festiana Efendi; Evawany Y Aritonang; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Ergogenic supplements are usually only consumed by athletes and its use is limited. However, this time not only consumed by athletes, but also began to be consumed by fitness participants because they want to increase their muscle mass quickly. The purpose of this study is to describe the consumption of ergogenic supplements and Mid Upper Arm Muscle Circumference (MUAMC) of Medan Sehat fitness center’s participants.          This research was a descriptive with cross sectional design. The method was used is the survey method by interviewing respondents directly using a questionnaire and MUAMC measurements by measuring the triceps thickness and MUAC respondents. Total respondents are 100 participants from 130 Medan Sehat fitness center’s participants  which is selected by purposive sampling with criteria such as adults aged 18 until 60 years, have followed fitness for a minimum of 1 month, willing to become respondents and can communicate well, and not ill.         The results showed 100 fitness participants who are respondents in this study, more respondents who did not take ergogenic supplements that 65 people (65%) compared to respondents who take ergogenic supplements only 35 people (35%). Respondents who take ergogenic supplements, most of them take ergogenic supplements every day as many as 24 people (68.6%). There are 23 people (35.4%) of respondents who did not take ergogenic supplements has below normal MUAMC.         The use of ergogenic supplements of the fitness of participants is not required because their frequency and duration of exercise are not too heavy so that the fulfillment of nutrients can still be met from daily food intake. Fitness participants should consider whether taking ergogenic supplements important. Keywords: Ergogenic Supplements,MUAMC, Fitness Participant